THE EFFECT OF RICE HUSK CHARCOAL ON THE GROWTH AND PRODUCTION OF WHITE CHILI CAYEY (Capsicum frutescens L) - Makalew, Evaristus; Naharia, Orbanus; Nanlohy, Fanny (Indonesian Biodiversity Journal, 2024)
The aim of this research is: to determine and analyze the effect of giving rice husk charcoal on the growth and production of white cayenne pepper plants (Capsicum frutescens L). The method used in this research is the experimental method with a completely randomized design (RAL) approach. This shows that rice husk charcoal and planting media have different average values for plant height, number of leaves, number of branches, number of fruit and weight of white cayenne pepper. At the 12th week of observation, the M2ASP2 treatment had the highest value compared to other treatments, namely124.65 ± 31.73cm. Meanwhile treatment M1 ASP 0has the lowest value, namely79.23 ± 21.9cm.